THE IMPLEMENTATION OF ACTIVE LEARNING ON EXPRESSING APOLOGY OF THE STUDENTS IN SEVENTH-GRADE OF MTSS ISTIQOMAH - Husaini Luftiah Erdani Sinaga; Muhammad Hadi’id Alifti; Emeliya Sukma Dara Damanik (E-LINK JOURNAL, 2022)
This research focused on analyzing the implementation of the active learning method on participation in the perspective of students in the seventh grade of MTsS Istiqomah. This study uses a qualitative descriptive approach to describe the analysis results from students' perspectives in the seventh grade of MTsS Istiqomah about the active learning method in expressing apology material. This study states that the active learning method is the proper method to use in learning expressing apology because it is not only listening to the teacher explain, but students can also take part in it. The researcher interviewed five students from the seventh-grade of MTsS Istiqomah. The sample was selected using the purposive sampling method. To obtain findings through analysis, the researcher arranged several questions to explore and receive information from respondents. The study results conclude that the active learning method is very appropriate to use in the learning process of expressing an apology.Keywords: Active learning, expressing apology, learning process